2021
DOI: 10.3390/ijms222111834
|View full text |Cite
|
Sign up to set email alerts
|

Fibulin 2 Is Hypermethylated and Suppresses Tumor Cell Proliferation through Inhibition of Cell Adhesion and Extracellular Matrix Genes in Non-Small Cell Lung Cancer

Abstract: Fibulins (FBLNs), interacting with cell adhesion receptors and extracellular matrix (ECM) components, play multiple roles in ECM structures and tissue functions. Abnormal expression of FBLN2, one of the fibulin family members, contributes to tumor initiation and development. However, the function of FBLN2 in human non-small cell lung cancer (NSCLC) has not yet been elucidated. In this study, we found that FBLN2 was downregulated in 9 out of 11 lung cancer cell lines compared to normal bronchial epithelial cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 63 publications
2
10
0
Order By: Relevance
“…Fibulin‐2 (FBLN2) is an extracellular glycoprotein and was initially discovered in embryonic endocardial cushion tissue and adult mouse and human heart valves, and FBLN2 may be involved in tissue development and remodelling 26,27 . According to reports, FBLN2 has been identified to exhibit tumour suppressor properties in several cancer types, such as breast cancer, 28 non‐small cell lung cancer, 29 and nasopharyngeal carcinoma 30 . In contrast, FBLN2 was reported to act as an oncogene in urothelial carcinoma 31 and colorectal cancer 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Fibulin‐2 (FBLN2) is an extracellular glycoprotein and was initially discovered in embryonic endocardial cushion tissue and adult mouse and human heart valves, and FBLN2 may be involved in tissue development and remodelling 26,27 . According to reports, FBLN2 has been identified to exhibit tumour suppressor properties in several cancer types, such as breast cancer, 28 non‐small cell lung cancer, 29 and nasopharyngeal carcinoma 30 . In contrast, FBLN2 was reported to act as an oncogene in urothelial carcinoma 31 and colorectal cancer 32 .…”
Section: Discussionmentioning
confidence: 99%
“…The FBLN2 gene encodes an extracellular matrix (ECM) protein, which binds multiple extracellular ligands and calcium [ 25 ], and it has a wide range of physiological functions. Some studies revealed a strong relationship between FBLN2 and the occurrence and progression of tumors [ 26 , 27 ]. Other studies reported that FBLN2 is likely associated with cardiovascular disease [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are also some proteins that overexpress in the NSCLC patients, which could become new targets in clinical trials. Fibulin2 (FBLN2) is decreased in the lung cancer cell lines, and the overexpression of FBLN2 would inhibit the activation of MAPK/ERK and AKT/mTOR signaling pathways, accompanied by the decreased migration and invasion of cells ( 64 ). This means that FBLN2 could be a potential biomarker for detecting NSCLC in the clinic.…”
Section: The Biological Features Of Lung Cancermentioning
confidence: 99%